2022
DOI: 10.3390/plants11162085
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation of Browsable Native Shrubs in New Zealand

Abstract: Information on the nutritive value and in vitro fermentation characteristics of native shrubs in New Zealand is scant. This is despite their potential as alternatives to exotic trees and shrubs for supplementary fodder, and their mitigation of greenhouse gases and soil erosion on hill-country sheep and beef farms. The objectives of this study were to measure the in vitro fermentation gas production, predict the parameters of the in vitro fermentation kinetics, and estimate the in vitro fermentation of volatile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…Protein content was generally low (<10%). Digestibility analysis suggested that animals consuming native shrubs would produce similar rumen methane emissions to those on pasture (Wangui et al 2022). Feed preference of some shrub species was greater than pasture.…”
Section: Natives As Alternative Foragesmentioning
confidence: 98%
“…Protein content was generally low (<10%). Digestibility analysis suggested that animals consuming native shrubs would produce similar rumen methane emissions to those on pasture (Wangui et al 2022). Feed preference of some shrub species was greater than pasture.…”
Section: Natives As Alternative Foragesmentioning
confidence: 98%